2006
DOI: 10.1073/pnas.0507066103
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteome analysis of the human mitotic spindle

Abstract: During cell division, the mitotic spindle segregates the sister chromatids into two nascent cells, such that each daughter cell inherits one complete set of chromosomes. Errors in spindle formation can result in both chromosome missegregation and cytokinesis defects and hence lead to genomic instability. To ensure the correct function of the spindle, the activity and localization of spindle associated proteins has to be tightly regulated in time and space. Reversible phosphorylation has been shown to be one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
262
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(287 citation statements)
references
References 52 publications
21
262
2
2
Order By: Relevance
“…Previous proteomics studies using isolated mitotic HeLa cell spindles or human embryonic stem cells have demonstrated that Hec1 is phosphorylated on Ser55 and Ser69 in vivo by undetermined kinases (Nousiainen et al, 2006;Malik et al, 2009;Brill et al, 2009;Olsen et al, 2010). We now include Ser44, Ser15 and Ser8 to the list of known in vivo N-terminal Hec1 phosphorylation sites (supplementary material Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous proteomics studies using isolated mitotic HeLa cell spindles or human embryonic stem cells have demonstrated that Hec1 is phosphorylated on Ser55 and Ser69 in vivo by undetermined kinases (Nousiainen et al, 2006;Malik et al, 2009;Brill et al, 2009;Olsen et al, 2010). We now include Ser44, Ser15 and Ser8 to the list of known in vivo N-terminal Hec1 phosphorylation sites (supplementary material Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We compared our results with several large phosphoproteomic datasets (6)(7)(8). Interestingly, at least 36 of our sites, or 50%, are known to be phosphorylated in vivo in HeLa cells.…”
Section: Identification Of Cdk1-cyclin B Substrates and Their Phosphomentioning
confidence: 99%
“…Prediction of high-likelihood kinase substrates can sometimes be achieved by using knowledge of the substrate sequence motif preferences of individual kinases, but only when these preferences are strong (4,5). Finally, thousands of in vivo phosphorylation sites from metazoan organisms have been identified in proteomic screens (6)(7)(8)(9), but for most of these sites the responsible upstream kinases remain unknown.…”
mentioning
confidence: 99%
“…1A, upper panel, labeled 1 in schematic), the abundance of which was reduced in the presence of lambda phosphatase (lower panel). As survivin is also phosphorylated by CDK1 during mitosis, 36,37 it is possible that CDK1 is a major contributor to the abundance of protein in this spot. Nevertheless, the data clearly demonstrate that survivin is phosphorylated in prometaphase cells.…”
Section: Human Survivin Is Phosphorylated By Aurora-b In Vivomentioning
confidence: 99%